Glutathione S‐transferase Pi 1 is a valuable predictor for cancer drug resistance in esophageal squamous cell carcinoma. Issue 2 (21st December 2018) - Ogino, Shinpei; Konishi, Hirotaka; Ichikawa, Daisuke; Matsubara, Daiki; Shoda, Katsutoshi; Arita, Tomohiro; Kosuga, Toshiyuki; Komatsu, Shuhei; Shiozaki, Atsushi; Okamoto, Kazuma; Kishimoto, Mitsuo; Otsuji, Eigo
Abstract : Esophageal squamous cell carcinoma (ESCC) is a lethal malignancy. However, there are few useful markers for diagnosis and treatment. Glutathione S‐transferase Pi 1 (GSTP1) has been reported as a predictor of malignancy or anticancer drug resistance in some cancers. We investigated the association of GSTP1 expression with the malignancy or drug resistance in ESCC cell lines and clinical tissue samples. Proliferation and apoptosis assays regarding GSTP1 expression were examined in ESCC cell lines. Proliferation of GSTP1 knockdown cells was significantly decreased ( P < .01), and the frequency of early apoptosis was increased ( P < .05). Invasion capacity of GSTP1 knockdown cells was slightly decreased in transwell assay. These results suggest that GSTP1 plays an important role in malignant potential. To examine the effects of GSTP1 on drug resistance, chemosensitivity assay and apoptosis assay under cisplatin exposure were carried out. Viability of GSTP1 knockdown cells treated with cisplatin was lower than that of control cells ( P < .01). Moreover, the frequency of early and late apoptosis in GSTP1 knockdown cells was markedly increased over that of control cells by cisplatin exposure ( P < .01). In immunohistochemistry assay of resected tissue samples, GSTP1 expression was significantly associated with clinical downstaging ( P = .04) in 72 ESCC patients with neoadjuvant chemotherapy. Furthermore, there was a significant association between GSTP1 expression in resected tissue and biopsy samples in 34 ESCC patients without neoadjuvant chemotherapy ( P = .02). In summary, GSTP1 was related to malignant potential and may be a predictive marker of drug resistance in ESCC patients. Abstract : Glutathione S‐transferase Pi 1 (GSTP1) promoted tumor growth and cancer drug resistance in esophageal squamous cell carcinoma (ESCC) cell lines. GSTP1 protein expression in resected ESCC tissues with neoadjuvant chemotherapy was significantly associated with clinical downstaging and correlated with that in biopsy samples.